Investigating the Determinants of Online Fashion Purchases: Insights into Consumer Intention in the E-Commerce Marketplace - Winny Alna Marlina; Fani Andriyani; Intan Intan (Jurnal Manajemen dan Kewirausahaan, 2024)
This research aims to analyze the factors influencing consumers' intentions to make online purchases on fashion e-commerce marketplaces in West Sumatra. The study employs quantitative methods, utilizing SEM-PLS. It adopts an explanatory research approach, focusing on causal study. The time horizon used in this study is one-shot (cross-sectional, 2023). Data collected for this study was through primary data and distributed questionnaires, using a non-probability sampling method. The population comprises all consumers in the fashion e-commerce marketplace in West Sumatra, with a total sample size of 225 respondents residing in the region. To increase consumer purchase intention in the online system, there needs to be innovation in the marketing strategy used, one of which is a strategy through social media. The research results revealed that internet self-efficacy, perceived aesthetics, and perceived benefits had a positive and significant effect on online purchase intentions, while perceived risk did not significantly influence online purchase intentions. Additionally, self-efficacy on the internet and perceived aesthetics had a positive and significant effect on perceived benefits. Pricing also positively influenced purchase intentions.